C.207C>G mutation in sepiapterin reductase causes autosomal dominant dopa-responsive dystonia. (December 2017) - Shalash, Ali S.; Rösler, Thomas W.; Müller, Stefanie H.; Salama, Mohamed; Deuschl, Günther; Müller, Ulrich; Opladen, Thomas; Petersen, Britt-Sabina; Franke, Andre; Hopfner, Franziska; Kuhlenbäumer, Gregor; Höglinger, Günter U.
Abstract : Objective: To elucidate the genetic cause of an Egyptian family with dopa-responsive dystonia (DRD), a childhood-onset dystonia, responding therapeutically to levodopa, which is caused by mutations in various genes. Methods: Rare variants in all coding exons of GCH1 were excluded by Sanger sequencing. Exome sequencing was applied for 1 unaffected and 2 affected family members. To investigate the functional consequences of detected genetic variants, urinary sepiapterin concentrations were determined by high-performance liquid chromatography. Results: A heterozygous rare nonsynonymous variant in exon 1 of sepiapterin reductase ( SPR, c.207C>G, p.Asp69Glu) was found in all affected family members. Urinary concentrations of sepiapterin were above the standard of normal controls in most SPR mutation carriers, suggesting functional biochemical consequences of the mutation. Variant filtering of all genes involved in the tetrahydrobiopterin pathway, required for levodopa synthesis, revealed an additional common variant in dihydrofolate reductase ( DHFR, rs70991108). The presence of both variants was significantly stronger associated with the biochemical abnormality and the clinical disease state as opposed to 1 variant only. Conclusions: The rare SPR mutation can cause autosomal dominant DRD with incomplete penetrance. The common DHFR variant might have synergistic effects on production of tetrahydrobiopterin and levodopa, thereby increasing penetrance.